Sustainable service through product knowledge delivery in Mediterranea Restaurants, Yogyakarta, Indonesia - Wicaksono, Agung; Suratman, Andriyastuti (Nur Science Institute, 2025)
This study aims to explore the strategic role of product knowledge in improving the quality of employees in providing services in the restaurant industry. Using a qualitative case study approach at Mediterranea Restaurant Yogyakarta, Indonesia, this study collected data through in-depth interviews and observations through seven key informants. Then, Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, display, and conclusion. The study's results indicate that product knowledge not only improves service competence but also helps employees deal with customer complaints, encourages purchasing decisions, and enables customers to make product purchases after conveying the meaning of the menu offered. This finding also confirms that systematic training based on on-job training and mentoring plays a key role in forming service competence. This study highlights the practical implications of providing customer products and services from an internal organizational perspective to see how restaurant management designs strategies and develops human resource learning factors based on knowledge-based service.